Determination of Flavonoids and Carotenoids and Their Contributions to Various Colors of Rose Cultivars (Rosa spp.) - Wan, Huihua; Yu, Chao; Han, Yu; Guo, Xuelian; Luo, Le; Pan, Huitang; Zheng, Tangchun; Wang, Jia; Cheng, Tangren; Zhang, Qixiang (Frontiers in Plant Science, 2019)
Rose is one of the most valuable ornamental crops worldwide. In this study, the composition of hydrophilic and lipophilic pigments in petals of six rose cultivars at seven developing stages was investigated using high performance liquid chromatography and mass spectrometry. Four anthocyanins, 20 flavonols, and 10 carotenoids were detected in petals of tested cultivars. Major individual anthocyanin, flavonol, and carotenoid were cyanidin/pelargonidin 3,5-diglucoside, kaempferol 3-O-rhamnoside, and (9Z)-violaxanthin, respectively. Significant differences were observed in pigments content in petals of different rose cultivars. The yellow petals of YI and GC exhibited no to very small amounts of anthocyanins, moderate amount of total flavonols, and highest content of total carotenoids. Similarly, pink petals of PF, WQ, and YX showed average concentration of total anthocyanins, highest concentration of total flavonols, and small amount of carotenoids. Further, orange petals of CH showed highest content of total anthocyanins, lowest content of total flavonols, and average content of total carotenoids. Correlation analysis demonstrated that there were many pigments influencing petal colors. Moreover, multiple linear regression indicated that pelargonidin 3,5-diglucoside, total anthocyanins and (9Z)-violaxanthin were the major factors. In addition, this study showed that orange cultivar CH, pink cultivar PF and yellow cultivar YI can have great potential as a natural source for the extraction of pelargonidin 3-O-glucoside, kaempferol 3-O-rhamnoside, and (9Z)-violaxanthin, respectively. These investigations would contribute toward understanding the mechanism on the development of flower colors and provide a theoretical basis for the breeding of rose with specific color.